Influence of Corporate Social Responsibility on Market Share: A Survey of the Telecommunication Firms in Kenya - Miyogoh, Wilkister Rakamba; Arasa, Robert; Ngui, Thomas (Stratford Peer Reviewed Journals and Book Publishing, 2021)
The telecommunications industry in Kenya contributes up to 10% to Gross Domestic Product.However, the Kenyan telecommunication industry is dominated by three operators that include Safaricom, Airtel and Telkom. This study soughtto determine the influence ofcorporate social responsibilityon marketshare in the telecommunication industry in Kenya withparticular focusonhow community social support, environmental responsibility, CSR economic expectations and consumer protection influence market share of the telecommunication industry. The study applied descriptive survey design. The study population was 123 telecommunication companies operating in Kenya. Data was collected was using structured questionnairesand analyzed using descriptive statistics, correlation and regression analyses by use of SPSS Version 25.0 software.Pearson correlation analysis revealed that community social support, environmental responsibility, CSR economic expectations and consumer protection had positive correlation with market share of the telecommunication industry in Kenya. Community social support, environmental responsibility, CSR economic expectations and consumer protection were found to explain 64.0% of market share of the telecommunication industry in Kenya. Consumer protection (β=.334) had the highest positive effect on market share, followed by CSR economic expectations (β=.277), community social support (β=.232) and environmental responsibilities (β=.211). Community social support, environmental responsibilities, CSR economic expectations and consumer protectionhad positive influence onmarket share of the telecommunication industry. The study concludes that community social support is a way to get back to the community by supporting the development of social amenities and services, environmental responsibility is at the core of environmental sustenance, consumer protectionand CSR economic expectations are important pillars driving telecommunication firms‟ market share. The telecommunication firms need to engage in active community social support via provision of social amenities, engage in activities that do not harm the environment particularly pollution, better methods of disposing used electronic items should be adopted by the telecommunication firms, there is need for a balance between firm‟s desire for gains and other social responsibilities highlighted in this study and the need for the telecommunication firms to prioritize the safety and wellness of the consumer by ensuring that goods sold are functional, safe and accompanied with adequate customer support.
Keywords: Corporate Social Responsibility; Market Share; Telecommunication Firms; Kenya